PENGARUH PENERAPAN CORPORATE GOVERNANCE, RETURN ON ASSET, DAN LEVERAGE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Vera Yuliani (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to examine the influence of Corporate Governance, Return on Assets and Leverage simultaneously or partially to Tax Avoidance on manufacturing companies listed in the Indonesia Stock Exchange period 2012-2016. The sample is determined by using purposive sampling with predetermined criterion, so that obtained by 9 manufacturing companies that qualify as sample. Data used secondary data. Data obtained from www.idx.co.id in the form of annual financial statements for the period 2012-2016. The analysis technique used is multiple linear regression method. Regression test results show that Corporate Governance with the proxy of Independent Commissioner and Quality Audit, ROA, and Leverage have a significant positive effect on Tax Avoidance. partially Independent Commissioner has a significant negative effect on tax evasion and leverage has a positive effect on tax evasion. The magnitude of influence Independent variables seen from the value of coefficient of determination (R2 of 0.176 which means KOM, KA, ROA and LEV gives positive influence on tax avoidance only 17.6% and 82.4% influenced by other variables outside the study. Keywords: Tax Avoidance, Komisaris Independen, Kualitas Audit, Return on Asset, Leverage